O processo de mudan??a organizacional no contexto de uma institui????o confessional de ensino - Morais, Valdirene Barreto de (2016)
Considering the speed with which the scenarios are now moving and the need for organizations to follow suit these scenarios, the objective of this study was to identify the influence of organizational communication in the change process in a Confessional institution of education. The study of communication and Organizational Change, had reference to the scholars of subjects. The methodology was qualitative, to get the results included the application of interviews, which were listed categories according to the repetition of themes and were also analyzed individually. The results indicate that communication should occupy a central space in the change process, through her objects are explained, the timing of implementation is analyzed and uncertainties are eased, it was found that a challenge will align organizational communication with the theory and the practice of school.